Measuring the Density of N\(_2\) Active Species in N\(_2\) –xCH\(_4\) Afterglows with x= (0-7.5)10\(^-4\) by Mass Spectrometry and Optical Spectroscopy at Low Gas Pressure - André Ricard; Anne-Marie Diamy; Jean-Claude Legrand (Plasmas Afterglows with N2 for Surface Treatments synthesis 2024, 2025)
The density of N-atoms in N2 pink and late microwave flowing afterglows has been investigated by mass spectrometry and NO titration. By optical spectroscopy, it has been obtained after NO titration the density of N2(B,11), N2(C,0) and N2+(B,0)) radiative states and of N2(A), N2+ metastable and ionic molecules. By introducing a few CH4 into N2, the density of C-atoms added to N-atoms is measured in the pink afterglow. The N2 pink afterglow was observed when the N2(B,v’=16-18) levels appeared after the autodissociative N2(B,v’=13-15) states, contrary to the late afterglow where the N2(B,v’=16-18) levels could not be detected.